2005
DOI: 10.1897/03-596.1
|View full text |Cite
|
Sign up to set email alerts
|

Feathers as a nondestructive biomonitor for persistent organic pollutants

Abstract: Keratinous tissues of mammals and humans, such as hair, have been used to determine the exposure to polychlorinated biphenyls (PCBs) and organochlorine pesticides. In the present study, we investigated the accumulation of persistent organic pollutants (POPs; PCBs, p,p'-DDT, p,p'-dichlorodiphenyldichloroethane [DDD], p,p'-dichlorodiphenyldichloroethylene [DDE], hexachlorobenzene [HCB], oxychlordane, trans-nonachlor, polybrominated diphenyl ethers, and polybrominated biphenyls [PBBs]) in feathers of the great ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 26 publications
5
73
2
Order By: Relevance
“…Sum PCBs concentrations were similar (median 50 ng/g, range 28-87 ng/g) to those in the common moorhen (mean±CI: 25±14 ng/g, range 3.5-81 ng/g), while sum DDT concentrations were rather low (median 4.1 ng/g, range 2.3-11 ng/g), even lower than concentrations reported in the common moorhen (mean±CI: 12±3.5 ng/g, range 6.6-26 ng/g). Overall, concentrations measured in the birds of this study (not including the common moorhen) were higher than concentrations measured by Dauwe et al (2005). Moreover, all organohalogenated pollutants (even PBDEs, HCB and CHLs) could be quantified in one single feather of the predatory birds under study.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Sum PCBs concentrations were similar (median 50 ng/g, range 28-87 ng/g) to those in the common moorhen (mean±CI: 25±14 ng/g, range 3.5-81 ng/g), while sum DDT concentrations were rather low (median 4.1 ng/g, range 2.3-11 ng/g), even lower than concentrations reported in the common moorhen (mean±CI: 12±3.5 ng/g, range 6.6-26 ng/g). Overall, concentrations measured in the birds of this study (not including the common moorhen) were higher than concentrations measured by Dauwe et al (2005). Moreover, all organohalogenated pollutants (even PBDEs, HCB and CHLs) could be quantified in one single feather of the predatory birds under study.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, birds feeding mainly in aquatic environments are expected to show lower OCPs levels, than birds feeding in terrestrial environments where pesticides are commonly applied. Dauwe et al (2005) have reported concentrations of organic pollutants in feathers of a small passerine bird, the great tit. PBDEs, HCB and CHLs could not be detected in feathers of great tits, similar to the results for the common moorhen in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations